2021
DOI: 10.1080/03670244.2021.1875456
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Isolation during COVID-19 Pandemic on Nutrition and Exercise Behaviors of Nursing Students

Abstract: This study aims to examine the effect of social isolation during COVID-19 pandemic on nutrition and exercise behaviors of nursing students. This descriptive study was conducted with nursing students of a university in eastern Turkey. The sample of the study consisted of 1,011 nursing students. The data were collected via e-mail using the Questionnaire of Descriptive Characteristics and the Nutrition Exercise Behavior Scale. Nutrition and exercise behaviors were affected by lockdown. During lockdown due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 58 publications
(59 reference statements)
0
32
0
16
Order By: Relevance
“…A subgroup analysis showed that changes were present in male outpatient caregivers and those under 40 years old. In this context, survey results among nursing students show a weight gain due to the pandemic [52], which was shown among Brazilian urologists as well [95]. This could be explained by a higher stress perception among nurses in comparison to doctors (cf.…”
Section: Eating Behaviourmentioning
confidence: 93%
See 2 more Smart Citations
“…A subgroup analysis showed that changes were present in male outpatient caregivers and those under 40 years old. In this context, survey results among nursing students show a weight gain due to the pandemic [52], which was shown among Brazilian urologists as well [95]. This could be explained by a higher stress perception among nurses in comparison to doctors (cf.…”
Section: Eating Behaviourmentioning
confidence: 93%
“…The lockdown restrictions led to an overall decreased physical activity among participants [108]. Although Tran et al [54] and Que et al [109] highlighted a protective effect of sufficient physical activity against anxiety disorders and depressive symptoms through their study among healthcare workers, including inpatient nurses, the COVID-19 pandemic led to an observed decrease in physical activity in the inpatient health sector among healthcare workers, urologists and nursing students [52,95,108]. In contrast, other study results showed that in the inpatient setting, healthcare workers used physical activity as a coping behaviour in the course of the experienced job demands of the pandemic [110].…”
Section: Physical Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…Participants in one study (two articles) were adult twins from the Washington State Twin registry [72,73]. Five studies invited all or a random sample of students from universities [74,76,84,88,92]. Another study only used data from students who used a university-intern movement tracking app [98].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven studies gave no information on the mean or median age of participating (older) adults [32,78,79,81,90,94,99]. The mean (or median) age of the subgroup of students ranged between 20.0 and 29.9 years [74,76,84,88,92,97,98]. Of the five studies investigating children and adolescents, three stated a mean age between 9.0 and 12.1 years [87,89,93], and two an age range of 5-17 years [86] and 15-18 years [95], respectively.…”
Section: Study Characteristicsmentioning
confidence: 99%